Efektivitas Model Problem Based Learning terhadap Pemahaman Konsep Matematika Peserta Didik - Muh. Sabar; Nur Khalisah Latuconsina; Andi Dian Angriani; Suharti; Badaruddin Amin (Al Asma: Journal of Islamic Education, 2023)
Increasing understanding of concepts is one of the main goals in learning mathematics. The Problem Based Learning (PBL) learning model is a model that can develop an understanding of mathematical concepts by solving real problems. This study aims to determine the effectiveness of the Problem Based Learning (PBL) model on students' understanding of mathematical concepts. The method used is quantitative with the type of quasi-experimental research and non-equivalent control group research design. The population in this study were all students of class VIII SMP Muhammadiyah Limbung, Gowa district, totaling 347 students. The instruments used to determine students' understanding of mathematical concepts are pretest and posttest. The data analysis technique used is descriptive and inferential statistical analysis with the t-test. The results showed that learning using the Problem Based Learning model effectively increased the understanding of mathematical concepts in class VIII students of SMP Muhammadiyah Limbung.